2010
DOI: 10.1177/019874291003600102
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of and Services Provided to Youth in Secure Care Facilities

Abstract: Youth who are incarcerated in secure detention and commitment settings display a complex array of educational, behavioral, and mental health issues that affect the services they require, as well as their responsiveness to interventions. Yet, seldom are these needs understood or taken into account when providing services in secure care settings. In this article, research documenting what is known regarding the characteristics of incarcerated youth is summarized. Current research on the use of evidence-based int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 73 publications
1
38
0
Order By: Relevance
“…Gagnon and Barber (2010) point out that juveniles with E/BD in secure care often experience difficulties while incarcerated because they lack basic cognitive and social skills. For example, Leone (1994) found that youth with disabilities received more behavioral incident reports, were more frequently restrained, and spent more time in confinement and segregation than youth without disabilities.…”
Section: Behaviormentioning
confidence: 99%
See 3 more Smart Citations
“…Gagnon and Barber (2010) point out that juveniles with E/BD in secure care often experience difficulties while incarcerated because they lack basic cognitive and social skills. For example, Leone (1994) found that youth with disabilities received more behavioral incident reports, were more frequently restrained, and spent more time in confinement and segregation than youth without disabilities.…”
Section: Behaviormentioning
confidence: 99%
“…Although believed to be a conservative number, Gagnon, Barber, Van Loan, and Leone (2009) estimate that 40% of youth in juvenile correction facilities have disabilities, which contrasts with the approximated 12% identified in public schools (Quinn, Rutherford, Leone, Osher, & Poirier, 2005). Since juveniles in secure settings often have academic deficits due to learning disabilities in both reading and mathematics (Gagnon & Barber, 2010), it is no surprise that detainees experience higher rates of school failure and lower academic performance compared with their same age peers. Krezmien, Mulcahy, and Leone (2008) examined reading and mathematics standardized academic achievement scores of 555 incarcerated male youth and found that the detained youth were approximately four years behind their same age general population peers.…”
Section: Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Mental health problems in this population are associated with further offending and these problems continue into adulthood, resulting in failure to mature into reasonably healthy and well-functioning adults [6,7] . Psychological researchers have found similar problems and s equelae among incarcerated young people in China who suffer from more serious mental health problems, such as anxiety and depression [8] .…”
Section: Introductionmentioning
confidence: 99%